Book Review: Peter Cleave, Data Wars: The Algorithmic State - Paul, Moon (Te Kaharoa, 2022)
In recent years, literature on indigenous issues has come to be dominated by two connected themes: the challenges arising from the experiences of colonisation; and the means of (re-) asserting indigenous culture, political influence, and identity. To some degree, the focus on these areas has come at the expense of other developments affecting indigenous groups (among others), particularly the rise of commercial and political forces that subvert the significance of the binary Western-indigenous model of analysis, and that present both material and conceptual challenges to notions of indigeneity. Among much else, the cultural and political ramifications of emerging virtual states on indigenous peoples is a topic of Professor Peter Cleave’s new book, Data Wars: The Algorithmic State.